Particulate manganese shuttling shapes molybdenum and thallium isotope compositions in surface sediments of the Arabian Sea oxygen minimum zone - Xinming Chen; Niels A.G. M. van Helmond; Bing Xia; Hainan Lu; Zili Zhao; Yu Zhang; Lulu Wang; Yi-Bo Lin; Feifei Zhang; Gert-Jan Reichart; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2026)

Graph attention-based decomposed-critic multi-agent deep reinforcement learning for multi-zone HVAC control - Chenghao Zhang; Xinli Wang; Kang Li; Lei Wang; Xinming Li; Lin Liu (Building and Environment, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Thermal runaway dynamics of LFP batteries in confined pressurized atmospheres: From triggering to gas evolution - Lin Yu; Yuhui Wang; Qing Wang; Kuo Wang; Jianqi Zhang; Xinming Qian (Chemical Engineering Journal, 2025)

An overlooked health risk of PM2.5: Elevated respiratory viral susceptibility revealed by assessing inflammatory and antiviral responses to chemical constituents - Shuyi Peng; Juying Lin; Wei Sun; Yaohao Hu; Baichuan Gou; Guohua Zhang; Wei Song; Bin Jiang; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Atmospheric Environment, 2025)

The threat of diaphragm closure to thermal runaway during battery charging - Jianqi Zhang; Tao Fan; Zhengnan Liu; Lin Yu; Yuhui Wang; FangZhou Li; Shuai Yuan; Chongye Chang; Kuo Wang; Ziwei Song; Xinming Qian; Qing Wang (Chemical Engineering Journal, 2025)

Neutrophils undergo migration and produce an antiviral response following porcine epidemic diarrhea virus infection - Yichao Ma; Xinming Qin; Jian Zheng; Xuebin Peng; Shiqi Liu; Ruoyang Lin; Baoyan Meng; Xiaojing Cui; Qian Yang (Veterinary Microbiology, 2025)

Base excision repair in human cancer: Emerging diagnostic and therapeutic target - Wenli Zhou; Xinming Jing; Ruyi Hang; Zheng Liu; Lin Cao; Mengxia Li (DNA Repair, 2025)

Integrating analytical solutions and U-Net model for predicting groundwater contaminant plumes in pump-and-treat systems - Xuehang Song; Inci Demirkanli; Zhangshuan Hou; Xinming Lin; Marinko Karanovic; Matt Tonkin; Delphine Appriou; Rob Mackley (Advances in Water Resources, 2025)

Deep learning MRI-based radiomic models for predicting recurrence in locally advanced nasopharyngeal carcinoma after neoadjuvant chemoradiotherapy: a multi-center study - Chunmiao Hu; Congrui Xu; Jiaxin Chen; Yiling Huang; Qingcheng Meng; Zhian Lin; Xinming Huang; Li Chen (Clinical & Experimental Metastasis, 2025)

Characteristics of ozone pollution and VOCs source analysis in the northern cities of Zhejiang, China - Yinglong Zhang; Xiaoxia Yang; Xu Lin; Ye Lu; Li Li; Xiaopei Xu; Jing Yuan; Fan Zhang; Xinglong Pang; Huanhuan Zhao; Xinming Zhu; Yaozong Shen; et al. (Atmospheric Pollution Research, 2025)

Winter wheat harvest detection via Sentinel-2 MSI images - Jibo Yue; Yihan Yao; Jianing Shen; Ting Li; Nianxu Xu; Haikuan Feng; Yihao Wei; Xin Xu; Yinghao Lin; Wei Guo; Yuanyuan Fu; Hongbo Qiao; et al. (International Journal of Remote Sensing, 2025)

A comparative study on the formation of nitrogen-containing organic compounds in cloud droplets and aerosol particles - Guohua Zhang; Tao Wang; Qinhao Lin; Kun Liu; Wei Sun; Duohong Chen; Lei Li; Xinming Wang; Xinhui Bi (Journal of Environmental Sciences, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Research on the explosive characteristics and suppression mechanisms of gas generation during thermal runaway of batteries in a charged state - Jianqi Zhang; Fangzhou Li; Lin Yu; Yuhui Wang; Kuo Wang; Chongye Chang; Minghui Li; Wenhao Hao; Xinming Qian (Chemical Engineering Journal, 2025)

Decreased net N nitrification rate constrains soil N availability during long-term Camellia oleifera cultivation - Tinghao Zong; Jingwei Ma; Xinming Guan; Yusong Lin; Yuqi Chen; Meiqi Wang; Jiaze Lv; Yichao Rui; Yang Chen; Lichao Wu; Sheng Lu (Applied Soil Ecology, 2025)

Molecular characteristics of organic matters in PM2.5 associated with upregulation of respiratory virus infection in vitro - Juying Lin; Wei Sun; Shuyi Peng; Yaohao Hu; Guohua Zhang; Wei Song; Bin Jiang; Yuhong Liao; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Journal of Hazardous Materials, 2025)

Comparison and identification of aroma components in 21 kinds of frankincense with variety and region based on the odor intensity characteristic spectrum constructed by HS–SPME–GC–MS combined with E-nose - Xinming Chen; Dandan Yang; Lin Huang; Mengqi Li; Jihai Gao; Can Liu; Xiaoming Bao; Zhizhi Huang; Jinhui Yang; Haozhou Huang; Dingkun Zhang; Runchun Xu (Food Research International, 2024)

Insight into the pyrolysis behavior of corn straw through TG-FTIR, Py-GC/MS experiments and ReaxFF MD simulations - Xiuxia Zhang; Xinming Liu; Meihua Xiao; Hongqing Feng; Riyi Lin; Xinwei Wang (Fuel, 2024)

On the transferability of residence time distributions in two 10-km long river sections with similar hydromorphic units - Jie Bao; Xuehang Song; Yunxiang Chen; Yilin Fang; Xinming Lin; Zhangshuan Hou; Zhuoran Duan; Huiying Ren; William Perkins; Xiaoliang He; Timothy Scheibe (Journal of Hydrology, 2024)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

A simple numerical simulation model can elucidate the key factors for designing a miniaturized ion trap mass spectrometer - Xinming Huo; Lin Gan; Xinyue Ding; Quan Yu; Bin Zhou; Jianhua Zhou; Xiang Qian (Analytica Chimica Acta, 2024)

Machine Learning Analysis of Impact of Western US Fires on Central US Hailstorms - Xinming Lin; Jiwen Fan; Yuwei Zhang; Z. Jason Hou (Advances in Atmospheric Sciences, 2024)

Simulating the land use change effects on non-point source pollution in the Duliujian River Basin - Xinming Jia; Yu Zhang; Sandylove Afrane; Jian Lin Chen; Pingjian Yang; Guozhu Mao (Environmental Geochemistry and Health, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

Identifying conservation and restoration priorities for degraded coastal wetland vegetations: Integrating species distribution model and GeoDetector - Jinlan Lin; Sixuan He; Xinming Liu; Zhongjian Huang; Meng Li; Bin Chen; Wenjia Hu (Science of The Total Environment, 2024)

New advance in biorenewable FDCA-based polyesters: Multiple scale-up from lab bench to pilot plant - Bo Wang; Zhu Tu; Xinyuan Zhang; Lin Sang; Wentao Chan; Lei Wang; Xinming Pu; Feng Ling; Min Qi; Zhiyong Wei (Chemical Engineering Journal, 2023)

The large decline in carbonate δ238U from a PETM section at Tingri (South Tibet) was driven by local sea-level changes, not global oceanic anoxia - Qinghai Zhang; Lin Ding; Xinming Chen; Gregory A. Brennecka; Yali Sun; Xuesong Ma; Bintao Gao; Qian Zhang; Helmut Willems (Earth and Planetary Science Letters, 2023)

Molecular characteristics, sources and transformation of water-insoluble organic matter in cloud water - Wei Sun; Ziyong Guo; Xiaocong Peng; Juying Lin; Yuzhen Fu; Yuxiang Yang; Guohua Zhang; Bin Jiang; Yuhong Liao; Duohong Chen; Xinming Wang; Xinhui Bi (Environmental Pollution, 2023)

An epipolythiodioxopiperazine alkaloid and diversified aromatic polyketides with cytotoxicity from the Beibu Gulf coral-derived fungus Emericella nidulans GXIMD 02509 - Miaoping Lin; Zhenzhou Tang; Jiaxi Wang; Humu Lu; Chenwei Wang; Yanting Zhang; Xinming Liu; Chenghai Gao; Yonghong Liu; Xiaowei Luo (Journal of Zhejiang University-SCIENCE B, 2023)

Predicting future well performance for environmental remediation design using deep learning - Xuehang Song; Huiying Ren; Zhangshuan Hou; Xinming Lin; Marinko Karanovic; Matt Tonkin; Vicky L. Freedman; Inci Demirkanli; Rob Mackley (Journal of Hydrology, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

Combined Culture and DNA Metabarcoding Analysis of Cyanobacterial Community Structure in Response to Coral Reef Health Status in the South China Sea - Jianhua Kang; Hala F. Mohamed; Xinming Liu; Lulu Pei; Shuhong Huang; Xiangyuan Lin; Xinqing Zheng; Zhaohe Luo (Journal of Marine Science and Engineering, 2022)
Cyanobacteria occupy an extraordinarily diverse array of ecological niches in coral reefs because they play multifaceted roles, including primary carbon and nitrogen fixation, calcification, nutrient cycling, and oxygen production, as well as coral reef degradation through skeletal biocorrosion and polymicrobial diseases. In this study, cyanobacterial diversity in sediment, water, and coral tissues were explored in relation to coral health status (slightly, moderately, and severely damaged) of coral reefs at Weizhou Island, South China Sea. Microscopy of taxa morphological characteristics was combined with 16S rRNA gene metabarcoding. Fifteen and forty-three cyanobacterial genera were identified based on universal prokaryotic 16S rRNA gene primers and cyanobacteria-specific 16S rRNA gene primers metabarcoding, respectively, indicating a more sophisticated efficiency of the latter. In addition, three out of seven cyanobacterial strains that were isolated and identified based on morphology and phylogeny could not be detected using either molecular method. Therefore, culture-based combined cyanobacteria-specific 16S rRNA gene metabarcoding are highly recommended in future routine surveys. There was a clear distinction in cyanobacterial assemblage composition among locations with different coral health statuses, with degraded reefs exhibiting approximately a 1.25-fold increase in species compared to healthy habitats. In addition, the spreading of potentially toxic cyanobacteria, such as Nostoc and Lyngbya, in the degraded reef implies putative links to reef degradation. This study provides novel insights into the taxonomical diversity of cyanobacteria in tropical coral reefs. Metabarcoding is recommended as an effective tool for revealing cyanobacterial diversity patterns and thereby providing critical information for the effective management of coral reef ecosystems.

Prohibitin Protein Expression During Spermatogenesis in the Large Yellow Croaker, Larimichthys crocea - Chenwen Lin; Xinming Gao; Jie Ni; Shengshuo Zhang; Cheng Liu; Shengyu Luo; Chen Du; Xuebin Zheng; Congcong Hou; Daojun Tang; Chundan Zhang; Junquan Zhu (Journal of Ocean University of China, 2022)

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

Effects of live rock on removal of dissolved inorganic nitrogen in coral aquaria - Yan Li; Xinqing Zheng; Xiaozhou Yang; Dangyun Ou; Rongcheng Lin; Xinming Liu (Acta Oceanologica Sinica, 2017)